Development of a Health Literacy Promotion Model for Older Adults in an Elderly School - Songthai, Nichakan; Chaichanawirote, Uraiwan; Sittiwong, Tipparat; Pakanta, Intira (NU Journal of Nursing and Health Sciences, 2024)
This research and development project aimed to develop a model for promoting health literacy in the prevention and control of non-communicable chronic diseases within elderly schools. Research methodology was divided into two phases: 1) Model Development phase emphasized on model drafting based on health literacy framework proposed by Sorensen et al., supplemented by reports on needs and situation analyses of health literacy promotion among older adults. This process involved focus group meetings with 10 stakeholders, and 2) Model Implementation phase focused on implementing the developed model with elderly school members and compared the average health literacy of the elderly. The evaluation involved 23 members from an elderly school, chosen through simple random sampling. Additionally, the assessment of stakeholders' satisfaction with the model were conducted in 15 stakeholders shared characteristics akin to Phase I participants. The research instruments, including semi-structured interview questionnaires, health literacy questionnaires, and satisfaction questionnaires, were developed by the researchers. Content validity was tested by three experts, resulting in the indices of congruence (IOC) ranging from 0.67 to 1.00. The reliability of the health literacy questionnaires was tested with data collected from 27 older individuals, achieving a Cronbach's alpha coefficient of 0.95. Qualitative data were analyzed using content analysis, while quantitative data were subjected to statistical analyses, including frequency, percentage, mean, standard deviation, and paired sample t-test.The revealed that: 1) the Health Literacy Promotion Model consisted of three key components: motivation building, knowledge dissemination on health behavior management, and training in health literacy and self-management skills; 2) Effect of the model: After participating in the model, the sample group exhibited a significant increase in their mean health literacy scores compared to their pre-experiment levels (t = 2.96, p = .007) ; and stakeholders expressed a high level of satisfaction with the developed model ( = 4.23, S.D. = 0.67). It is suggested that the developed model utilize in other elderly schools with similar context to promote health literacy of older adults.